Cannabidiol (CBD): Perspectives from Pinterest. (1st October 2020) - Merten, Julie Williams; Gordon, Benjamin T.; King, Jessica L.; Pappas, Calista
Abstract: Background: Pinterest, a widely used social media platform, has shaped how people seek and share health information. Cannabidiol (CBD), a non-psychoactive component of cannabis is marketed as a treatment for many conditions and sales rose to more than 820 million in 2017. Yet CBD is mostly unregulated, legality is murky, and many of the health claims are not scientifically proven. Purpose: This content analysis examined how CBD products were portrayed on Pinterest. Methods : In 2018, using the search terms cannabidiol and CBD, researchers sampled every fifth pin to collect 226 relevant pins. A codebook was developed, pilot tested, and used to code pins. Results : The majority (91.6%) of pins positively portrayed CBD with many claiming a physical or mental benefit including anxiety, depression, pain, and inflammation relief. Most pins did not (98.2%) address potential side effects or recommend dosage. In this sample, user engagement was high with 85.2% of pins being saved and links to commercial sites selling CBD products, personal blogs, and social media accounts. Conclusions : Social media has become a powerful source of health information. This study revealed widespread acceptance of the use of CBD products with minimal information from reliable public health sources represented.